2020
DOI: 10.1097/hpc.0000000000000243
|View full text |Cite
|
Sign up to set email alerts
|

Oral Antiplatelet Therapy Administered Upstream to Patients With NSTEMI

Abstract: Objective: To describe from a noninterventional registry (Utilization of Ticagrelor in the Upstream Setting for Non-ST-Segment Elevation Acute Coronary Syndrome), the short-term ischemic and hemorrhagic outcomes in patients with non-ST elevation myocardial infarction (MI) are managed with a loading dose (LD) of a P2Y 12 inhibitor (P2Y 12 i) given at least 4 hours before diagnostic angiography and delineation of coronary anatomy. Prior data on the effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Sixteen studies with major bleeding events were included in the subgroup analysis (52,056 patients with NSTE-ACS) ( 4 , 5 , 11 13 , 15 17 , 19 , 21 26 , 28 ). The results of the inconsistency test showed that the inconsistency was not significant ( I 2 = 0.04, P = 0.851); therefore, the consistency model was used for the analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Sixteen studies with major bleeding events were included in the subgroup analysis (52,056 patients with NSTE-ACS) ( 4 , 5 , 11 13 , 15 17 , 19 , 21 26 , 28 ). The results of the inconsistency test showed that the inconsistency was not significant ( I 2 = 0.04, P = 0.851); therefore, the consistency model was used for the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining number of articles was 123. Studies that did not meet the inclusion or exclusion criteria, or had unclear expressions were further eliminated by reading the full text, and 21 articles were obtained (4,5,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29), including 13 RCTs (4,5,12,14,16,(18)(19)(20)(21)(23)(24)(25)(26) and eight observational studies (11,13,15,17,22,(27)(28)(29). Literature retrieval and screening processes were carried out in accordance with the PRISMA guidelines; the specific process of screening is shown in Figure 1.…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations